Prescribing Pattern and Safety Profile of Biological Agents for Psoriasis in Real-World Practice: A Four-Year Calabrian Pharmacovigilance Analysis - Caterina De Sarro; Francesca Bosco; Agnese Gagliardi; Lorenza Guarnieri; Stefano Ruga; Antonio Fabiano; Laura Costantino; Antonio Leo; Caterina Palleria; Chiara Verduci; Vincenzo Rania; Michael Ashour; et al. (MDPI AG, 2024)
Background: The treatment of psoriasis has made considerable progress with biologicals, including tumor necrosis factor inhibitors, and recently, monoclonal antibodies inhibiting directly interleukin (IL) 17, IL-23, or both IL-12/23. Newer biologicals are directed to the interleukin pathway and appear to improve complete or near-complete clearance. The newer biologicals have also been shown to have an excellent safety profile. However, despite experience with patients having confirmed the results obtained in clinical trials, there are still few data on using the newer biologicals. Methods: The present active study aimed to prospectively evaluate safety profiles and persistence of some biologicals in a multicenter pharmacovigilance study, that enrolled 733 patients treated with a biologic drug in five Calabrian hospital units. Informative and treatment persistence evaluations with predictors for suspension and occurrence of adverse events (AEs) were executed. In particular, reasons for treatment discontinuation in our program take account of primary/secondary failure or development of an AE. Results: AEs occurred in 187/733 patients and serious AEs (SAEs) were identified in 5/733 patients. An number of 182/733 patients showed a primary/secondary inefficacy. The AEs and SAEs were described with adalimumab, infliximab, and etanercept but not with abatacept, brodalumab, tildrakizumab, golinumab, ixekizumab, guselkumab, risankizumab, secukinumab, and ustekinumab. Conclusions: Our analysis, although limited by a small sample size and a short-term follow-up period, offers suitable data on commonly used biological agents and their safety, interruption rate, and the attendance of SAEs. Real-world studies should be carried out to evaluate other safety interests.